Modeling of Two-Phase Flow through a Rotating Tube with Twin Exit Branches - Sun-Wen Cheng; Wen-Jei Yang (International Journal of Rotating Machinery)
A numerical model is proposed to determine the dynamic behavior of single-phase and twophase, two-component flows through a horizontal rotating tube with identical twin exit branches. The working fluid, oil, enters the tube through a radial duct attached at one end and exits into open air through the twin radial branches, one located at midway and the other at the end of the tube. The branch-to-tube diameter ratio, rotational speed, and total oil flow rate are varied. It is experimentally revealed in previous study that the air cavitation occurs at lower speeds, leading to a two-phase flow with the air-oil ratio (void fraction) varying with the rotating speed. A unique characteristic in two-phase flow, i.e., hysteresis, is found to exist in both oil flow rates and inlet pressure. In theoretical modeling, the governing flow equations are incorporated by empirical equations for hydraulic head losses. The predicted and measured exit oil flow rates are compared with good agreement in both the single-phase and annular flow regimes. Only qualitative agreement is achieved in the bubbly and bubbly-slug flow regimes. The model can be applied to improve the design and thus enhance the performance of automatic transmission lines, and the cooling efficiency of rotating machines and petroleum drilling process.